843 Reproducible, MoA-reflecting reporter-based bioassays to enable drug development of biosimilars and biobetters. (10th December 2020) - Nelson, Jeffrey; Moravec, Richard; Li, Dun; Wilkinson, Jennifer; Fan, Frank; Cong, Mei
Abstract : Background: Cytokines and growth factors are small immunomodulatory proteins secreted by a wide variety of cells (e.g. fibroblasts, endothelial and stromal cells) that regulate surrounding cells via autocrine, paracrine or endocrine mechanisms. Immunocytokines are a promising class of activators of the immune system, with the potential to be used alone or in combination with other therapeutic agents to treat a variety of disease including autoimmunity and cancer. This class of biologics includes FDA-approved cytokine therapies (e.g. IFN, IL-2 and Epo) as well as an increasing number of biologics designed to block cytokine activity. The latter class of biologics includes basiliximab (IL-2R), tocilizumab and sarilumabad (IL-6R), siltuximab (IL-6), ustekinumab and its biosimilars (IL-12/IL-23 p40), secukinumab (IL-17A), bevasizumab (VEGF), and denosumab (RANKL). Pharmaceutical pipelines include an increasing number of biosimilar and biobetter molecules with sustained and targeted activities with a goal to improve drug potency, patient tolerance and clinical response. Methods: Quantitative and reproducible functional bioassays are critical for the development and manufacture of biologics drugs targeting cytokine and growth factor pathways. In many cases, existing bioassays rely on the use of primary cells and measurement of complex endpoints. These assays are highly variable, difficult to implement, and often fail to yield data quality required for drug development in a quality-controlled environment. To address this problem, we have developed a suite of bioluminescent luciferase-based reporter bioassays that can be used to quantitatively measure the activity of specific cytokines and growth factors, including: IL-2, IL-6, IL-12, IL-15, IL-17, IL-23, VEGF and RANKL. Results: These mechanism of action (MOA) reflecting bioassays exhibit the required performance metrics for use in potency and stability studies. Importantly, these bioassays have been optimized in a thaw-and-use cell format, which eliminates the need for cell culture and ensures high reproducibility, convenience and transferability. Conclusions: In summary, bioluminescent reporter-based bioassays offer significant advantages over primary cell-based bioassays and are valuable tools for the development and manufacturing of novel biologics targeting cytokine and growth factor pathways.